Performance evaluations of ICI cancellation schemes in OFDM systems. - Syed Yusof, Sharifah Kamilah; Fisal, Norsheila; Muladi, Muladi (2005)

(untitled)
OFDM is a successful technique in wireless communication system. Frequency offset in OFDM systems leads to loss of orthogonality among subcarriers, which resulted in intercarrier interference (10) to occur. Another main problem of OFDM is the occurrence of high PAPR. To mitigate ICI problem, ICI self-cancellation scheme and frequency domain partial response coding has been proposed. In this paper, we evaluate the performance of ICI self-cancellation schemes and the integer-coefficients partial response coding (PRC). ICI self-cancellation data allocation of (XkXk+1=-X k) has the best PAPR performance while the data allocation of (X kXk+1=-Xk) has the most CIR enhancement The integer coefficients PRC outperform the ICI self-cancellation schemes in terms of bandwidth efficiency and in the BER performance especially at high E/N o.